Sevoflurane pretreatment alleviates hypoxia-reoxygenation-induced myocardial cell injury by upregulating miR-21-5p - Saiwen Qiu; Hui Chen; Qifang Jiang (Frontiers in Cardiovascular Medicine)
BackgroundThis study investigates the preventive benefits of sevoflurane against myocardial ischemia-reperfusion (I/R) injury, focusing on its effect on the modulation of miR-21-5p.MethodsIn the clinical study, patients with a history of myocardial ischemia or other conditions requiring surgery were enrolled. Before surgery, the patients were anesthetized with either sevoflurane or propofol. The expression levels of IMA, H-FABP, IL-1β, TNF-α, and IL-6 were also examined. Additionally, the expression of miR-21-5p and its relationships with IMA and H-FABP. A cardiomyocyte hypoxia/reoxygenation (H/R) cell model was created for the in vitro tests. The cells were treated with or without sevoflurane and then transfected with inhibitors of miR-21-5p or a negative control (NC). Evaluations were conducted on cell viability, apoptosis ratio, and oxidative stress indicators (MDA, SOD, and ROS). Furthermore, the expression levels of miR-21-5p, apoptotic markers (BCL-2, BAX), myocardial damage markers (IMA, H-FABP), and inflammatory agents (TNF-α, IL-1β, IL-6) were quantified.ResultsIn patients with a history of myocardial ischemia, sevoflurane reduced myocardial I/R injury. These patients also showed upregulation of miR-21-5p, which expression positively linked with levels of IMA. Moreover, in H/R treated cardiac cells, sevoflurane markedly reduced the expression of BAX, MDA, ROS, SOD, inflammatory factor and the apoptotic ratio. Nevertheless, inhibition of miR-21-5p abolished these protective effects. Furthermore, in H/R myocardial cells, sevoflurane increased BCL-2 expression and cell survival; these effects were also countered by blocking miR-21-5p.ConclusionMechanistically, we demonstrate for the first time that sevoflurane alleviates myocardial cell injury in myocardial I/R by upregulating miR-21-5p, thereby reducing inflammation, apoptosis, and oxidative stress in myocardial cells. This finding provides a potential therapeutic target for improving myocardial I/R.